Contextual teaching and learning: Upaya optimalisasi kemampuan literasi matematis - Putri, Chantika Yuspia; Hendriana, Heris; Fitrianna, Aflich Yusnita (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The purpose of this study was to improve students mathematical literacy skills in statistics by appliying the Contextual Teaching and Learning (CTL) approach. Students of SMP Negeri 2 Padalarang became the population in this study. Thirty students of class VIII-A served as the experimental group and thirty students of class VIII-I served as the control group. This study used a non-equivalent control group design with quasi-experimental research methodology. This study included pretest, action, and posttest. This research tool used a written test to collect information about the improvement of students’ mathematical literacy skills. Data analysis was carried out by conducting normality test, homogeneity test and mean test in order to obtain conclusions. The findings of this study show that the improvement of mathematical literacy skills of students whose learning uses the Contextual Teaching and Learning (CTL) approach is better the those who use ordinary learning.